MUSIQUE DAN: La musique dans la pensee et la vie sociale d'une socidte africaine, by Hugo Zemp, Cahiers de l'Homme, Nouvelle Serie XI, Paris, Mouton, 1971. pp. 320, illus., maps, tables, song texts, glossary, bibliography and discography - Blacking, John (International Library of African Music, 1973)
pages: 98-99
Keywords: African Music